Carriage of Neisseria meningitidis and other Neisseria species among children and young adults in Paraguay. Issue 12 (1st November 2019) - Chamorro, Gustavo; Ibarz-Pavon, Ana Belén; Kawabata, Aníbal; León, María Eugenia; Orrego, Verónica; Nagai, Minako; Gabastou, Jean Marc
Abstract : Introduction. Colonization by Neisseria meningitidis is the pre-requisite for the development of disease. We present the findings of a cross-sectional investigation onto the oropharyngeal carriage of N. meningitidis and Neisseria species in the population aged 3 to 21 in Paraguay. Aim. Carriage prevalence by age groups, risk factors associated with carriage, and phenotypic and genotypic characteristics of strains are described. Methodology. We collected 2011 oropharyngeal swabs from consenting participants aged 3–21 years. Infants were recruited at immunization clinics, and older children and young adults were identified at schools and universities. A single oropharyngeal swab was collected and processed for the identification and isolation of Neisseria . Additionally, participants, or their legal guardian if these were minors, were requested to fill a standardized questionnaire. Results. N. meningitidis was isolated in 42/2011 (2.1 %) participants, while other Neisseria spp. were identified in 306/2011 (15.2 %) subjects: N. cinerea and N. lactamica were identified in 39/2011 (1.9 %) and 43/2011 (2.2 %), respectively. Meningococcal strains belonged to ten different clonal complexes, of which six are associated with invasive disease (ST-32/ET5 complex, ST-11/ET37 complex, ST-103 complex, ST-167 complex, ST-35 complex and ST-41/44 complex/lineage 3). Conclusion. Prevalence of N. meningitidis carriage was low compared to that reported from other settings, however, the overall carriage of Neisseria spp. (including N. meningitidis ) was comparable to meningococcal carriage prevalence reported in the literature. This study is the first of its kind conducted in Paraguay, and one of the few known in the Southern Cone of Latin America.